Knowledge, awareness and practice regarding familial hypercholesterolaemia among primary care physicians in Malaysia: The importance of professional training. (October 2018) - Azraii, Ahmad Baihaqi; Ramli, Anis Safura; Ismail, Zaliha; Abdul-Razak, Suraya; Mohd-Kasim, Noor Alicezah; Ali, Norsiah; Watts, Gerald F.; Nawawi, Hapizah
Abstract: Background and aims: This study aimed to determine knowledge, awareness and practice (KAP) regarding familial hypercholesterolaemia (FH) among Malaysian primary care physicians (PCP), and to compare KAP between PCP with postgraduate qualification (PCP-PG-Qual) and PCP without PG qualification (PCP-noPG-Qual). Methods: This was a cross-sectional study involving PCP with ≥1-year working experience in Malaysian primary care settings. An adapted and validated 25-item FH-KAP questionnaire was disseminated during primary care courses. Total score for each domain was calculated by summing-up the correct responses, converted into percentage scores. Normality distribution was examined and comparisons of mean/median percentage scores were made between the two groups of PCP. Results: A total of 372 PCP completed the questionnaire. Regarding knowledge, 77.7% correctly defined FH. However, only 8.3% correctly identified coronary artery disease risk in untreated FH. The mean percentage knowledge score was significantly higher in PCP-PG-Qual compared to PCP-noPG-Qual (48.9, SD ± 13.92 vs. 35.2, SD ± 14.13), t (370) = 8.66, p < 0.001. Regarding awareness, 39% were aware of the NICE FH guideline and only 27.2% were aware of FH diagnostic criteria. The median percentage awareness score was significantly higher in PCP-PG-Qual compared to PCP-noPG-Qual (15.4, IqR ± 23.08 vs. 7.7, IqR ± 11.54), p = 0.013. Regarding practice, only 19.1% stratified FH patients as high risk irrespective of other risk factors. The mean percentage practice score was significantly higher in PCP-PG-Qual compared to PCP-noPG-Qual (52.4, SD ± 12.92 vs. 42.7, SD ± 16.63), t(370) = 9.65, p < 0.001. Conclusions: Substantial gaps in FH-KAP among Malaysian PCP were identified, with PCP-PG-Qual having better knowledge, awareness and practice than PCP-noPG-Qual, emphasising the importance of professional training and certification. Highlights: The first study which determined FH knowledge, awareness and practice (KAP) among Malaysian primary care physicians (PCP) using a valid and reliable tool, and compared FH KAP between PCP with postgraduate (PG) qualification and those without. Malaysian PCP were good in defining FH and considered themselves as the most effective healthcare provider in early detection of FH. Gaps were found in knowledge on prevalence, inheritance and risk of CAD; awareness of clinical guidelines and diagnostic criteria; and practice on CAD risk stratification. PCP with PG qualification have better KAP regarding FH compared to those without. This study supports the need for compulsory vocational training for all Malaysian PCP where educational module on FH can be included.